Implementing positive psychology interventions to promote students’ English speaking performance at Thanh Dong University - Nguyen, Van Thang; Nguyen, Kieu Oanh Thi (Frontiers in Education, 2026)
Speaking skills are crucial in second language acquisition (SLA) as they enable learners to communicate effectively, express ideas, and engage in meaningful interactions. Positive psychology (PP) plays a vital role in enhancing speaking performance by fostering a supportive, motivating environment that reduces anxiety and boosts confidence. Integrating PP strategies, such as those grounded in the PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) model, promotes student engagement, motivation, and emotional well-being, all of which are essential for sustained improvement in language proficiency. This quasi-experimental study explores the impact of integrating PP strategies, based on Seligman’s (2011) PERMA model, on the students’ English-speaking performance at Thanh Dong University. Employing a mixed-methods approach, the research compares an experimental class (EC) exposed to PP interventions with a control class (CC) under conventional teaching methods. The findings revealed a significant post-intervention improvement in the EC’s speaking scores—particularly in vocabulary, fluency, and discourse management—emphasizing the implementation of PP strategies. The study also highlights the creation of a supportive learning environment, enriched through diverse thematic discussions, fostering motivation and engagement. Despite challenges, such as diverse student preferences, the study emphasizes the effectiveness of PP strategies, contributing to innovative language pedagogy.